Pengaruh Financial Knowledge, Financial Attitude, Dan Financial Management Terhadap Financial Satisfaction Masyarakat Lumajang - Nehemia Parham; Nanik Linawati (Sanskara Manajemen Dan Bisnis, 2022)
This study aims to examine the effect of financial knowledge, financial attitude, and financial management on financial satisfaction citizen of Lumajang. This study uses primary data taken from distributing questionnaires using google form to citizen of Lumajang who live in Lumajang and have stable income. The sample that obtain in this study is 100 respondent. The technique used in this study is Partial Least Square using the SmartPLS 3.0 program. The result of this study are variables of financial knowledge have significant effect on financial satisfaction, financial attitude have significant effect on financial satisfaction, and financial managament have significant effect on financial satisfaction .